2018
DOI: 10.1021/acs.biochem.8b01231
|View full text |Cite
|
Sign up to set email alerts
|

Human Indoleamine 2,3-Dioxygenase 1 Is an Efficient Mammalian Nitrite Reductase

Abstract: The heme enzyme indoleamine 2,3-dioxygenase-1 (IDO1) catalyzes the first reaction of l-tryptophan oxidation along the kynurenine pathway. IDO1 is a central immunoregulatory enzyme with important implications for inflammation, infectious disease, autoimmune disorders, and cancer. Here we demonstrate that IDO1 is a mammalian nitrite reductase capable of chemically reducing nitrite to nitric oxide (NO) under hypoxia. Ultraviolet–visible absorption and resonance Raman spectroscopy showed that incubation of dithion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
(197 reference statements)
1
16
0
Order By: Relevance
“…Similar to Mb and Hb, the heme in IDO1 is in a pentacoordinate state, which may account for the increased rates, as discussed above. A contrasting feature, in comparison with other heme-containing nitrite reductases, is that the nitrite reductase activity of IDO1 is enhanced in alkaline conditions (pH 8), which Lim and colleagues speculate may be due to the close proximity of histidine residues potentially capable of donating a proton (Lim et al, 2019). These initial observations have been made in recombinant human IDO1, and further studies are required to assess the in vivo relevance of these findings.…”
Section: Molybdenum-containing Oxidase Enzymesmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to Mb and Hb, the heme in IDO1 is in a pentacoordinate state, which may account for the increased rates, as discussed above. A contrasting feature, in comparison with other heme-containing nitrite reductases, is that the nitrite reductase activity of IDO1 is enhanced in alkaline conditions (pH 8), which Lim and colleagues speculate may be due to the close proximity of histidine residues potentially capable of donating a proton (Lim et al, 2019). These initial observations have been made in recombinant human IDO1, and further studies are required to assess the in vivo relevance of these findings.…”
Section: Molybdenum-containing Oxidase Enzymesmentioning
confidence: 98%
“…Indoleamine 2,3-Dioxygenase 1. Very recently, it has been demonstrated that indoleamine 2,3-dioxygenase 1 (IDO1), a cytosolic heme enzyme involved in the initial and rate-limiting step of L-tryptophan metabolism in the kynurenine pathway, is capable of reducing nitrite to •NO under anaerobic conditions (Lim et al, 2019). Similar to Mb and Hb, the heme in IDO1 is in a pentacoordinate state, which may account for the increased rates, as discussed above.…”
Section: Molybdenum-containing Oxidase Enzymesmentioning
confidence: 99%
“…Nitrite reductase activities have been described for several metalloproteins and metal-containing enzymes known for different functions. These comprise hemoglobin [ 37 , 47 ], myoglobin [ 48 ], cystathionine β-synthase [ 49 ] and indoleamine 2,3-dioxygenase 1 [ 48 ]. Even though the latter enzyme is known for its melatonin-oxidizing property, there is no reason to assume a functional cross-connection in this place.…”
Section: Nitric Oxide Its Congeners and Reactive Productsmentioning
confidence: 99%
“…Therefore, a drug that blocks the signalling activity of IDO1 in combination with its catalytic site may improve IDO1-targeting immunotherapy. Recently, it was discovered that under anaerobic conditions IDO1 is an efficient nitrite reductase capable of generating NO [161]. This study provides new insights into the role of IDO1 as a novel enzyme source of NO in tumours.…”
Section: Amino Acid Metabolismmentioning
confidence: 79%